Answer:
243
Step-by-step explanation:
STEP 1: Evaluate the variables
9(2 + (5)(5))
STEP 2: Then from there you can multiply the equation
18 + 225 = 243
The equation of circle is
![x ^{2} + y ^{2} - 16 = 0](https://tex.z-dn.net/?f=x%20%5E%7B2%7D%20%20%2B%20y%20%5E%7B2%7D%20-%2016%20%3D%200)
![\quad \huge \quad \quad \boxed{ \tt \:Answer }](https://tex.z-dn.net/?f=%5Cquad%20%5Chuge%20%5Cquad%20%5Cquad%20%5Cboxed%7B%20%5Ctt%20%5C%3AAnswer%20%7D)
![\qquad \tt \rightarrow \: x = 3](https://tex.z-dn.net/?f=%5Cqquad%20%5Ctt%20%5Crightarrow%20%5C%3A%20x%20%3D%203)
____________________________________
![\large \tt Solution \: :](https://tex.z-dn.net/?f=%20%5Clarge%20%5Ctt%20Solution%20%20%5C%3A%20%3A%20)
![\qquad \tt \rightarrow \: log_{2}(x - 1) log_{2}(x + 5) = 4](https://tex.z-dn.net/?f=%5Cqquad%20%5Ctt%20%5Crightarrow%20%5C%3A%20%20log_%7B2%7D%28x%20-%201%29%20%20log_%7B2%7D%28x%20%2B%205%29%20%20%3D%204)
![\qquad \tt \rightarrow \: log_{2} \{(x - 1)(x + 5) \} = 4](https://tex.z-dn.net/?f=%5Cqquad%20%5Ctt%20%5Crightarrow%20%5C%3A%20%20log_%7B2%7D%20%5C%7B%28x%20-%201%29%28x%20%2B%205%29%20%5C%7D%20%3D%204)
[ log (x) + log (y) = log (xy) ]
![\qquad \tt \rightarrow \: ( x - 1)(x + 5) = {2}^{4}](https://tex.z-dn.net/?f=%5Cqquad%20%5Ctt%20%5Crightarrow%20%5C%3A%20%28%20x%20-%201%29%28x%20%2B%205%29%20%3D%20%20%7B2%7D%5E%7B4%7D%20)
![\qquad \tt \rightarrow \: {x}^{2} + 5x - x - 5 = 16](https://tex.z-dn.net/?f=%5Cqquad%20%5Ctt%20%5Crightarrow%20%5C%3A%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%205x%20-%20x%20-%205%20%3D%20%2016)
![\qquad \tt \rightarrow \: {x}^{2} + 4x - 5 - 16 = 0](https://tex.z-dn.net/?f=%5Cqquad%20%5Ctt%20%5Crightarrow%20%5C%3A%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%204x%20-%205%20-%2016%20%3D%200)
![\qquad \tt \rightarrow \: {x}^{2} + 4x -21 = 0](https://tex.z-dn.net/?f=%5Cqquad%20%5Ctt%20%5Crightarrow%20%5C%3A%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%204x%20-21%20%3D%200)
![\qquad \tt \rightarrow \: {x}^{2} + 7x - 3x - 21 = 0](https://tex.z-dn.net/?f=%5Cqquad%20%5Ctt%20%5Crightarrow%20%5C%3A%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%207x%20-%203x%20-%2021%20%3D%200)
![\qquad \tt \rightarrow \: x(x + 7) - 3(x + 7) = 0](https://tex.z-dn.net/?f=%5Cqquad%20%5Ctt%20%5Crightarrow%20%5C%3A%20%20x%28x%20%2B%207%29%20-%203%28x%20%2B%207%29%20%3D%200)
![\qquad \tt \rightarrow \: (x + 7)(x - 3) = 0](https://tex.z-dn.net/?f=%5Cqquad%20%5Ctt%20%5Crightarrow%20%5C%3A%20%28x%20%2B%207%29%28x%20-%203%29%20%3D%200)
![\qquad \tt \rightarrow \: x = - 7 \: \: or \: \: x = 3](https://tex.z-dn.net/?f=%5Cqquad%20%5Ctt%20%5Crightarrow%20%5C%3A%20x%20%3D%20%20-%207%20%5C%3A%20%20%5C%3A%20or%20%5C%3A%20%20%5C%3A%20x%20%3D%203)
The only possible value of x is 3, since we can't operate logarithm with a negative integer in it.
![\qquad \tt \rightarrow \: x = 3](https://tex.z-dn.net/?f=%5Cqquad%20%5Ctt%20%5Crightarrow%20%5C%3A%20x%20%3D%203)
Answered by : ❝ AǫᴜᴀWɪᴢ ❞
Answer:
Y
=
−
3
x
+
5 5
x
−
5
y
=
-
3
Step-by-step explanation:
the question is already substituted